1997
DOI: 10.1007/s000180050088
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant synthesis of mouse Zn 3 - ? and Zn 4 - ? metallothionein 1 domains and characterization of their cadmium(II) binding capacity

Abstract: Genetic engineering, coupled with spectroscopic analyses, has enabled the metal binding properties of the alpha and beta subunits of mouse metallothionein 1 (MT) to be characterized. A heterologous expression system in E.coli has led to high yields of their pure zinc-complexed forms. The cadmium(II) binding properties of recombinant Zn4-alpha MT and Zn3-beta MT have been studied by electronic absorption and circular dichroism. The former binds Cd(II) identically to alpha fragments obtained from mammalian organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 28 publications
5
77
0
Order By: Relevance
“…First, the in vivo synthesized M-MT4, M-␣MT4, and M-␤MT4 (where M represents zinc, cadmium, and copper) aggregates and the recombinant Cd-MT1 and Cd-␣MT1 species, not previously studied, were characterized. Second, the reaction pathways of the in vitro zinc/cadmium and zinc/copper replacement processes undergone by the three Zn-MT4 peptides at pH 7 were determined using the rationale previously applied for MT1 (21)(22)(23)(24). Detailed analysis of the spectroscopic (CD and UV-visible electronic absorption) sets of data recorded during these titrations provided information on the number of metal-MT species generated, their stoichiometry, and their degree of folding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the in vivo synthesized M-MT4, M-␣MT4, and M-␤MT4 (where M represents zinc, cadmium, and copper) aggregates and the recombinant Cd-MT1 and Cd-␣MT1 species, not previously studied, were characterized. Second, the reaction pathways of the in vitro zinc/cadmium and zinc/copper replacement processes undergone by the three Zn-MT4 peptides at pH 7 were determined using the rationale previously applied for MT1 (21)(22)(23)(24). Detailed analysis of the spectroscopic (CD and UV-visible electronic absorption) sets of data recorded during these titrations provided information on the number of metal-MT species generated, their stoichiometry, and their degree of folding.…”
Section: Resultsmentioning
confidence: 99%
“…According to the composition of the recombinant samples reported here, only the CD spectra of the Cd 4 -␣MT4, Cd 7 -MT1, and Cd 4 -␣MT1 solutions can be considered representative of the CD fingerprints of these species (data included in Fig. 4), all showing the characteristic derivative-shaped band at ϳ250 nm of the Cd-MT aggregates (21,22). In contrast, the CD spectra of the recombinant Cd-MT4 and Cd-␤MT4 samples (data included in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-ml fractions were collected and analyzed for protein content by their absorbance at 254 nm. Validation of these recombinant synthesis procedures has been fully confirmed for mammalian MT (32). Aliquots of the protein-containing fast performance liquid chromatography fractions were analyzed by 15% SDS-PAGE and stained by Coomassie Blue.…”
Section: Mt Expression and Analysis Of The Recombinant Zinc And Coppementioning
confidence: 98%
“…It was found that MT levels in mammalian tissues under physiological conditions could be rather high to harbour important implications for MTs operation in Zn and redox metabolism (Capdevila et al, 1997;Capasso et al, 2005;Kelly et al, 2006). Different substances besides metals, such as fungicides fenhexamid, mancozeb, and also hydrogen peroxide, induce the elevation of MT content in fish (Viarengo et al, 1999;Cavaletto et al, 2002;Paris-Palacios et al, 2003;Mosleh et al, 2005;Kang, 2006).…”
Section: Non-enzymatic Antioxidants: Glutathione and Other Scavengersmentioning
confidence: 99%